2012
DOI: 10.1590/s1806-83242012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells express proteins involved in the local invasiveness of odontogenic myxoma

Abstract: Little is known about the histogenesis of the odontogenic myxoma (OM). Dental pulp stem cells could be candidate precursors of OM because both OM and the dental pulp share the same embryological origin: the dental papilla. For the purpose of comparing OM and stem cells, this study analyzed the expression of two proteins related to OM invasiveness (MMP-2 and hyaluronic acid) in human immature dental pulp stem cells (hIDPSCs). Three lineages of hIDPSCs from deciduous and permanent teeth were used in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…Inactivating mutations of PRKAR1A gene were also found in patients diagnosed with OM, and this gene regulates a subunit type 1A of cAMP‐dependent PKA 62 . Interestingly, some previous studies suggested that dental pulp stem cells may be the precursors of OM, but more studies should be performed 65,66 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivating mutations of PRKAR1A gene were also found in patients diagnosed with OM, and this gene regulates a subunit type 1A of cAMP‐dependent PKA 62 . Interestingly, some previous studies suggested that dental pulp stem cells may be the precursors of OM, but more studies should be performed 65,66 …”
Section: Discussionmentioning
confidence: 99%
“…62 Interestingly, some previous studies suggested that dental pulp stem cells may be the precursors of OM, but more studies should be performed. 65,66 Maybe, the frequency difference between study populations with higher prevalence in Asian and American population may be explained by genetic susceptibility and polymorphism of some gene groups, as happens in odontogenic keratocystic tumour 67 and ameloblastoma; 68 however, no study evaluated this characteristic for OM.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is related to the histogenesis of the odontogenic neoplasms. [7] Majority of tumors occur in jaw bearing areas therefore the word odontogenic is prefixed to reflect its odontogenic origin. The resemblance to mesenchyme of developing tooth or the periodontal ligament suggests its histogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of matrix metalloproteinases 2 (MMP2) expression was found in cell lines derived from OM tumor. [7]…”
Section: Discussionmentioning
confidence: 99%
“…Em situações patológicas da cavidade bucal, as MMPs têm sido relacionadas a tipos de neoplasias (Miyagi et al, 2012), doença periodontal (Sorsa et al, 2004), inflamação pulpar (Hannas et al, 2007) e cárie (Tjäderhane et al, 1998). Nesse último exemplo, ainda na década de 80 e sem indicar especificamente as MMPs, Dayan et al (1983) realizaram um estudo preliminar comparando a atividade colagenolítica em dentina humana cariada e não-cariada e encontraram maior atividade enzimática em dentina cariada, sugerindo que as enzimas responsáveis pela degradação de colágeno seriam ativadas durante o processo de cárie dental.…”
Section: Metaloproteinasesunclassified